Quantification of Malondialdehyde in Atmospheric Aerosols: Application of the Thiobarbituric Acid Method - David H. Gonzalez; Suzanne E. Paulson (Aerosol and Air Quality Research)
Abstract Based on available toxicity data, malondialdehyde (MDA; O=CHCH2CH=O) has been designated as a potential human carcinogen. A handful of studies suggest that MDA forms in the gas and aerosol phase in the troposphere, potentially contributing to inhalation toxicity, yet it has never been quantified in ambient air. The thiobarbituric acid (TBA) acid assay for MDA has been used as a marker for reactive oxygen species (ROS), oxidative stress, and lipid peroxidation in biological samples for decades. Here we apply the TBA assay to estimate the amount of MDA in ambient fine particulate matter (PM2.5) for the first time, in samples containing biomass burning/urban aerosol from Fresno, CA, and urban aerosol from Los Angeles. We found 0.31–0.75 ng m–3 MDA in the particle phase, similar to the low end, but up to three orders of magnitude lower than the upper end of reported concentrations of the common C3 oxygenates methylglyoxal and malonic acid. Additionally, we investigated the response in the TBA assay to seven common small oxygenates, and found interference only from acrolein, but–only when the acrolein was at millimolar concentrations, well above expected levels in aerosol extracts. In sum, this work suggests that MDA is present at moderate levels in biomass burning and urban aerosols; more may be in the gas phase.